The retirement plan : a novel - Hincenbergs, Sue (William Morrow, an imprint of HarperCollins Publishers, 2025)
"Three middle-aged best friends turn to murder in order to collect on their husbands' life insurance policies...but are unaware that their husbands have a devious plan of their own, in this darkly funny debut perfect for fans of Thursday Murder Club and Everyone in My Family Has Killed Someone"--